2021
DOI: 10.21660/2021.88.gxi279
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Subsurface Structure of Landslide Area Based on Microtremor Observation in the Hojoshima, Nawashiro and Amedaki Area, Tottori, Japan

Abstract: Investigating the subsurface structure of a landslide area is important for considering the hazards of slope disasters. In this study, microtremor exploration was conducted in three areas (Hojoshima, Nawashiro, and Amadaki) in Tottori Prefecture, which were judged to have landslide topography, and the subsurface structure was estimated as well. The target areas were based on a landslide topography distribution map published by the National Research Institute for Earth Science and Disaster Prevention. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The analysis of geophysical and geotechnical data combined with the support of spatial data (DTM) allowed the reconstruction of a detailed geological model of the Theilly landslide. The HVSR investigation led to the identification of two important natural peaks, one at high frequencies (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), which made it possible to identify the thickness of the material reworked by anthropic intervention, and one at low frequencies (3.3-4.3 Hz), attributable to a deeper level (20-30 m), characterised by a high Vs value (>800 m/s).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of geophysical and geotechnical data combined with the support of spatial data (DTM) allowed the reconstruction of a detailed geological model of the Theilly landslide. The HVSR investigation led to the identification of two important natural peaks, one at high frequencies (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), which made it possible to identify the thickness of the material reworked by anthropic intervention, and one at low frequencies (3.3-4.3 Hz), attributable to a deeper level (20-30 m), characterised by a high Vs value (>800 m/s).…”
Section: Discussionmentioning
confidence: 99%
“…In this work, geophysical techniques such as single-station environmental seismic noise (analysed according to the horizontal-to-vertical spectral ratio, HVSR or H/V, [26]) and GPR measurements were used to support geotechnical investigations (geognostic survey such as the standard penetration test and geotechnical in situ and laboratory tests) to return a detailed geological model for subsequent numerical modelling. The H/V spectral ratio measurements are increasingly used in landslide areas to identify the potential slip surface [27][28][29][30]. In fact, they make it possible to identify deep surface discontinuities separating materials characterised by a strong acoustic impedance (loose material versus.…”
Section: Introductionmentioning
confidence: 99%
“…Pumice, a glassy volcanic rock with high pores, is white or pale grey to brown in color; pumice sand is subject to pulverization during seismic events, which may potentially induce landslides and liquefaction. Several regions with active volcanoes, including Indonesia, Japan, New Zealand, and the United States, exhibit pumice layers in multiple locations at some points attributed to the failure, which causes landslides or liquefaction phenomena [3][4][5][6][7]. To fully understand the behavior of pumice particles, it is crucial to consider both the general properties of pumice and the failures resulting from the presence of the pumice layer.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have effectively used microtremor measurements to understand the dynamic characteristics of soil and assess its seismic vulnerability [5][6][7][8][9][10][11]. For instance, Noguchi et al [5] clarified the damage caused by the 2018 East Hokkaido Iburi Earthquake through the HVSR method.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Noguchi et al [5] clarified the damage caused by the 2018 East Hokkaido Iburi Earthquake through the HVSR method. Furthermore, microtremor surveys helped estimate landslide sediment layer thickness in three landslide areas of Tottori Prefecture, Japan [6]. Nishimura et al [7] conducted microtremor investigations in the landslide area of Tandikat, West Sumatra, Indonesia, finding the predominant periods of the microtremor HVSR range between 0.1-0.4 s. Wijayanto et al [8] also demonstrated how local conditions, particularly the landform effect, significantly influence Vs30 in Gunungkidul, Yogyakarta, Indonesia.…”
Section: Introductionmentioning
confidence: 99%